The OEIS mourns the passing of Jim Simons and is grateful to the Simons Foundation for its support of research in many branches of science, including the OEIS.
login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A361305 Expansion of A(x) satisfying A(x) = x + A(x)^2*(1 + A(x))^3. 8
1, 1, 5, 23, 123, 700, 4170, 25677, 162101, 1043603, 6825429, 45222437, 302892681, 2047499720, 13950769772, 95710823820, 660609751890, 4584018016679, 31960334260971, 223782306725768, 1572921720684820, 11094267854522250, 78499108540111380, 557041048588402170 (list; graph; refs; listen; history; text; internal format)
OFFSET
1,3
LINKS
FORMULA
G.f. A(x) = Sum_{n>=1} a(n)*x^n satisfies:
(1) A(x) = Series_Reversion( x - x^2*(1+x)^3 ).
(2) A(x) = x + A(x)^2*(1 + A(x))^3.
(3) A(x) = x + Sum_{n>=1} d^(n-1)/dx^(n-1) x^(2*n) * (1+x)^(3*n) / n!.
(4) A(x) = x * exp( Sum_{n>=1} d^(n-1)/dx^(n-1) x^(2*n-1) * (1+x)^(3*n) / n! ).
(5) A(x) = x + Series_Reversion( Series_Reversion( x*(1+x)^(3/2) ) - x^2 )^2.
From Vaclav Kotesovec, Mar 09 2023: (Start)
Recurrence: 283*(n-3)*(n-2)*(n-1)*n*(3869140*n^3 - 39431172*n^2 + 133221959*n - 149076999)*a(n) = 4*(n-3)*(n-2)*(n-1)*(1199433400*n^4 - 14022813420*n^3 + 59620648652*n^2 - 107988096753*n + 68872774500)*a(n-1) + 6*(n-3)*(n-2)*(3718243540*n^5 - 52766330452*n^4 + 294066223701*n^3 - 803084308634*n^2 + 1072900001465*n - 559958090580)*a(n-2) + 12*(n-3)*(2453034760*n^6 - 43397123748*n^5 + 316599139024*n^4 - 1218191215329*n^3 + 2605017314614*n^2 - 2932345787601*n + 1355713586640)*a(n-3) + 5*(5*n - 21)*(5*n - 19)*(5*n - 18)*(5*n - 17)*(3869140*n^3 - 27823752*n^2 + 65967035*n - 51417072)*a(n-4).
a(n) ~ 1/(2 * sqrt(Pi*(1 + s)*(1 + 8*s + 10*s^2)) * n^(3/2) * r^(n - 1/2)), where r = 0.1321273811013026086255933373480102325835852282463... and s = 0.2180852364825231879900920777342190033594997222087... are real roots of the system of equations r + s^2 * (1+s)^3 = s, s * (1+s)^2 * (2+5*s) = 1. (End)
a(n+1) = Sum_{k=0..n} binomial(n+k+1,k) * binomial(3*k,n-k)/(n+k+1). - Seiichi Manyama, Aug 24 2023
EXAMPLE
G.f.: A(x) = x + x^2 + 5*x^3 + 23*x^4 + 123*x^5 + 700*x^6 + 4170*x^7 + 25677*x^8 + 162101*x^9 + 1043603*x^10 + ...
such that A(x) = x + A(x)^2 * (1 + A(x))^3.
Related series.
A(x)^2 = x^2 + 2*x^3 + 11*x^4 + 56*x^5 + 317*x^6 + 1876*x^7 + 11499*x^8 + 72352*x^9 + 464585*x^10 + ...
(1 + A(x))^3 = 1 + 3*x + 6*x^2 + 22*x^3 + 105*x^4 + 555*x^5 + 3151*x^6 + 18735*x^7 + 115200*x^8 + 726530*x^9 + ...
PROG
(PARI) {a(n)=polcoeff(serreverse(x-x^2*(1+x)^3+x*O(x^n)), n)}
for(n=1, 30, print1(a(n), ", "))
(PARI) {Dx(n, F)=local(D=F); for(i=1, n, D=deriv(D)); D}
{a(n)=local(A=x); A=x+sum(m=1, n, Dx(m-1, x^(2*m)*(1+x+x*O(x^n))^(3*m)/m!)); polcoeff(A, n)}
for(n=1, 30, print1(a(n), ", "))
(PARI) {Dx(n, F)=local(D=F); for(i=1, n, D=deriv(D)); D}
{a(n)=local(A=x+x^2+x*O(x^n)); A=x*exp(sum(m=1, n, Dx(m-1, x^(2*m-1)*(1+x+x*O(x^n))^(3*m)/m!))); polcoeff(A, n)}
for(n=1, 30, print1(a(n), ", "))
CROSSREFS
Sequence in context: A359915 A362568 A121636 * A200028 A020032 A293088
KEYWORD
nonn
AUTHOR
Paul D. Hanna, Mar 08 2023
STATUS
approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified May 23 21:14 EDT 2024. Contains 372765 sequences. (Running on oeis4.)